Peroxisome Proliferator Activated Receptor-α Agonist Slows the Progression of Hypertension, Attenuates Plasma Interleukin-6 Levels and Renal Inflammatory Markers in Angiotensin II Infused Mice - Justin L. Wilson; Rong Duan; Ahmed El-Marakby; Abdulmohsin Alhashim; Dexter L. Lee (PPAR Research)
The anti-inflammatory properties of PPAR-α plays an important role in attenuating hypertension. The current study determines the anti-hypertensive and anti-inflammatory role of PPAR-α agonist during a slow-pressor dose of Ang II (400 ng/kg/min). Ten to twelve week old male PPAR-α KO mice and their WT controls were implanted with telemetry devices and infused with Ang II for 12 days. On day 12 of Ang II infusion, MAP was elevated in PPAR-α KO mice compared to WT (161±4 mmHg versus 145±4 mmHg) and fenofibrate (145 mg/kg/day) reduced MAP in WT + Ang II mice (134±7 mmHg). Plasma IL-6 levels were higher in PPAR-α KO mice on day 12 of Ang II infusion (30±4 versus 8±2 pg/mL) and fenofibrate reduced plasma IL-6 in Ang II-treated WT mice (10±3 pg/mL). Fenofibrate increased renal expression of CYP4A, restored renal CYP2J expression, reduced the elevation in renal ICAM-1, MCP-1 and COX-2 in WT + Ang II mice. Our results demonstrate that activation of PPAR-α attenuates Ang II-induced hypertension through up-regulation of CYP4A and CYP2J and an attenuation of inflammatory markers such as plasma IL-6, renal MCP-1, renal expression of ICAM-1 and COX-2.